EFFECT OF MITRAL REGURGITATION ON CHRONIC HEART FAILURE COURSE AND STRUCTURE-FUNCTIONAL HEART STATE - V. N. Larina; B. Y. Bart; M. P. Mikhaylusova; B. N. Mamtsev (Столичная издательская компания, 2016)
Aim. To evaluate chronic heart failure (CHF) course, functional and structural heart changes in patients with functional mitral regurgitation (MR) of various degrees. Material and methods. A total of 104 outpatients (60-85 y. o.) with CHF of functional class II-IV by NYHA and functional MR of I-II degrees and MR of III-IV degrees were included into the study groups. Results: Patients in both groups were comparable in sex, age, CHF duration, body mass index, systolic and diastolic blood pressure, clinical state by the clinical state scale, quality of life, anxious and depressive status. The majority of patients with MR III had significant left ventricle (LV) systolic dysfunction (p=0,029), severe CHF course (p=0,034), received furosemide (p=0.004) and digoxin (p=0,004). They had significant increase in end-diastolic dimension (p<0,001), end-systolic dimension (p<0,001), left atrium (p=0,004), end-diastolic volume (p<0,001), end-systolic volume (p<0,001), pulmonary artery pressure (p<0,001), decrease in LV relative wall thickness (p=0,021) and LV ejection fraction (p<0,001). Patients of this group were hospitalized because of CHF decompensation and ischemic heart disease exacerbation more often (p=0,045). Conclusion. MR can be considered as one of sensitive predictors of LV geometry and function alteration in CHF patients and play an important role in symptoms development.